Identification of races of Helminthosporium sativum of wheat in Brazil - Mehta, Y. R. (Pesquisa Agropecuaria Brasileira, 2014)
Ninety-six monoconidial isolates of H. sativum were obtained from 41 municipal regions comprising five different states and as many as 51 different cultivars. Initially, 45 out of 96 isolates were tested against 40 wheat cultivars in the seedling stage; and based on the reaction pattern, a set of thirteen differential wheat cultivars was established. This set of differentials was further used to test the rest of the 51 isolates and a total of 32 different races were identified. The identified races were given serial numbers. Twenty-three races were identified from Paraná, 4 from São Paulo, 3 from Rio Grande do Sul, 1 from Mato Grosso and 1 from Brasilia, DF. Race 9 was most predominant in the states of Paraná, São Paulo and Rio Grande do Sul.